Development of solar digital thermometer - Mohd Alias Sani, Yaacob (2009)
Solar energy is one of the renewal energy to generate electricity. It produces electricity by heat engine or photovoltaic cell that converts the solar energy directly into electrical power. Nowadays, solar technology was use for electrical space heating and cooling in active and passive solar buildings, day lighting, hot water, thermal energy for cooking, and high temperature process heat for industrial purposes. In this project, the electric powers that have been produces from the solar panel will be use as an energy source to charge the digital thermometer battery. Mean that, the digital thermometer can operate although there is no sunlight in the period of time. To supply the required voltage to the digital thermometer, a regulator is needed to produce the required output voltage from the batteries. The project includes the analysis about the solar panel that will be used, build the circuit and program for the digital thermometer and develop the charger for the battery. For the digital thermometer, the LM35 had been used to measure the temperature. It can measure the temperature range; 0-99 degree Celsius. PIC 16F872 been used to read the voltage produce from LM35 and display it by seven segment as temperature in degree Celsius. The target of this project is to develop the solar digital thermometer that can show the surrounding temperature.